2020
DOI: 10.12965/jer.2040384.192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of creative dance-based exercise on gait performance in adolescents with cerebral palsy

Abstract: The purpose of this study is to explore the feasibility and therapeutic potential of creative dance (CD) based exercise as a rehabilitation intervention for adolescents with cerebral palsy (CP). Participants were 10 adolescents with spastic CP (mean age, 17.5± 2.12 years; Gross Motor Function Classification System levels I [n= 3] and II [n= 7]). Outcome measures included the Gross Motor Function Measure-88 (GMFM-88; dimensions D and E), spatiotemporal gait parameters, lower limb range of motion during walking,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 35 publications
0
24
0
1
Order By: Relevance
“…According to the current evidence, dancing can improve balance, postural stability, strength, functional mobility, and rigidity and provide social interaction. Studies involving children with CP reported that dance improved motor abilities, such as motor control, gross motor function, balance, and gait, while enhancing selfconfidence, body image, and a sense of accomplishment (11)(12)(13)(14). Moreover, dance can enhance brain plasticity by recruiting different motor, somatosensory, emotional, and cognitive areas (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the current evidence, dancing can improve balance, postural stability, strength, functional mobility, and rigidity and provide social interaction. Studies involving children with CP reported that dance improved motor abilities, such as motor control, gross motor function, balance, and gait, while enhancing selfconfidence, body image, and a sense of accomplishment (11)(12)(13)(14). Moreover, dance can enhance brain plasticity by recruiting different motor, somatosensory, emotional, and cognitive areas (15).…”
Section: Introductionmentioning
confidence: 99%
“…Tango (21), salsa (22), and tap dance (23), which featured participants to imitate or memorize a particular dance sequence, contribute to enhanced fitness, gait performance, and balance in people with Parkinson's disease (PD) and multiple sclerosis (MS). Also, creative dance (CD), including improvisational dance, and Bartenieff, Feldenkrais, and Laban methods, enhanced balance and mobility in children with CP (12)(13)(14), the elderly (24,25), and other populations with neurological disorders. Since CD focuses on exploration and creative ability to explore new and possible movements by learning to control the body (26), participants may move voluntarily by developing their own movement (25).…”
Section: Introductionmentioning
confidence: 99%
“…Significant increases in muscle strength and walking speed were found in [107] when rousing music was played during a resistance exercise. Improvements in the ROM of the hip and ankle, stride length, walking speed, cadence and step can also be found in interventions in which participants completed a dance-based exercise [47].…”
Section: Global Discussionmentioning
confidence: 98%
“…Indeed, large numbers of exercises can be found in the scientific literature that have demonstrated their efficiency in improving cardio-respiratory and muscular endurance without the need for any special equipment. For instance, for people with CP in GMFCS level I, or the equivalent in the ICF scale, these exercises include running [45], the shuttle-run game [46] or dancing [47]; for GMFCS I-III, activities included walking (gait) [45], stepping updown [26,48], sit-to-stand, crawling [42] and squatting [49]; for levels up to GMFCS level IV, we added the strengthening interventions of the knee extensor, hip flexor and ankle dorsiflexors [43].…”
Section: Recommended Exercises and Equipmentmentioning
confidence: 99%
“…The body movements performed by patients were free and may be induced by the emotion generated by dance. However, many studies have been focused on the physical benefits of dance on CP (due to motor impairments, such as balance, postural control, aerobic fitness, and gait performance) [ 15 , 36 , 37 , 38 , 39 ]. Thus, the present study can generate a line of investigation based on the benefits of dance on brain activity related to the emotionality of inclusive dance regardless of the motor complexity of the practice.…”
Section: Discussionmentioning
confidence: 99%